Time-serial analysis of deep neural network models for prediction of climatic conditions inside a greenhouse - Jung, Dae-Hyun; Kim, Hyoung Seok; Jhin, Changho; Kim, Hak-Jin; Park, Soo Hyun (ELSEVIER SCI LTD, 2020)
Greenhouses provide controlled environmental conditions for crop cultivation but require careful management to ensure ideal growing conditions. In this study, we tested three deep-learning-based neural network models (Artificial neural network, ANN; Nonlinear autoregressive exogenous model, NARX; and Recurrent neural networks - Long short-term memory, RNN-LSTM) to determine the best approach to predicting environmental changes in temperature, humidity, and CO2 within a greenhouse to improve management strategies. This study determined the prediction performance for time steps from 5 to 30 min and showed that the accuracy of the time-based algorithm gradually decreased as prediction time increased. The best model for all datasets was RNN-LSTM, even after 30 min, with an R-2 of 0.96 for temperature, 0.80 for humidity, and 0.81 for CO2 concentration. The results of this study show that it is possible to apply deep-learning-based prediction models for more precisely managing greenhouse.
Keywords: MICROCLIMATE; PARAMETERS; DESIGN; CFD